2010
DOI: 10.1177/1352458509356367
|View full text |Cite
|
Sign up to set email alerts
|

The association between California Verbal Learning Test performance and fibre impairment in multiple sclerosis: evidence from diffusion tensor imaging

Abstract: The California Verbal Learning Test (CVLT) is recognized as a standard clinical tool for assessing episodic memory difficulties in multiple sclerosis (MS), but its neural correlates have not yet been examined in detail in this patient population. We combined neuropsychological examination and diffusion tensor imaging (DTI) analysis in a group of MS patients (N = 50) and demographically matched healthy participants (N = 20). We investigated the degree of impairment of the uncinate fascicle (UF), the superior lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 52 publications
6
45
1
Order By: Relevance
“…To our knowledge, retrieval abilities, operationalized as the difference between free and cued recalls, have only rarely been reported in association with the CVLT in MS [27]. In the past, most authors compared delayed recall and recognition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To our knowledge, retrieval abilities, operationalized as the difference between free and cued recalls, have only rarely been reported in association with the CVLT in MS [27]. In the past, most authors compared delayed recall and recognition.…”
Section: Discussionmentioning
confidence: 99%
“…In previous group studies, executive memory difficulties in MS have been widely reported [8,[26][27][28] and have generally been described as encoding impairments [8,23]. Some authors are operationalized this deficit as a pathological score for both cued recalls and delayed recognition [28,26], although a storage deficit could also explain this long-term profile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spectroscopy can be used to detect metabolites that reflect axonal/neuronal integrity and has been used as a measure of neuroprotective effects [103] and excitotoxicity [104]. Diffusion tensor imaging can be used to monitor tract-specific changes that may be more closely linked to clinical measures [105,106] and may be particularly powerful when combined with functional measures, such as functional MRI [107]. T1/T2 relaxation is another quantitative approach that may provide a better metric for diffuse brain changes occurring beyond traditional white matter regions [108] and to quantify myelin content [109].…”
Section: New Approachesmentioning
confidence: 99%